Financial accounting and reporting - Elliott, Barry; Elliott, Jamie (Hoboken, NJ : Pearson, 2022)
'Financial accounting is the accurate recording of all transactions and combining these into a statement which shows the performance for an accounting period which is normally a year and a statement which shows the resources and liabilities at the end of the period. Financial reporting presents the performance, the resources and liabilities to the stakeholders in accordance with International Financial Reporting Standards. It is a dynamic area, intellectually demanding and full of interest. It aims to inform and provide the information in way that holds management to account and is'decision useful' by making inter-period and interfirm comparisons more accessible. We see it as extremely important that the text should reflect this and be kept current'--
Revised edition of the authors's Financial accounting and reporting, [2019]
Includes bibliographical references and index.
Keywords: Accounting; Financial statements